Позиція польських антикомуністичних урядів в питанні державно-територіального статусу малопольські всходнєй (Західної України та Західної Білорусі) в 1939–1945 рр. (аспекти геополітики та міжнародного права). Частина 2. Від розриву дипломатичних відносин (1943 р.) до радянсько-польських угод 1945 р. - Макарчук, Володимир; Makarchuk, Volodymyr (Видавництво Львівської політехніки, 2021)
Розглянуто міжнародно-правові аргументи та безпосередню діяльність польських емігрантських урядів В. Сікорського (жовтень 1939 – 4 липня 1943), С. Миколайчика (липень 1943 – листопад 1944), Т. Арцишевського (1944–1947) у питанні визначення післявоєнних кордонів Польщі, зокрема й відтинку з Українською РСР. Зроблено спробу оцінити ефективність їхньої діяльності. Уже восени 1939 р. сформувалися основні контури зовнішньої політики емігрантського уряду та цілісний набір міжнародно-правових аргументів, якими він оперуватиме упродовж усієї Другої світової війни і після її завершення: Pacta sunt servanda. Німецький напад на Польщу 1 вересня 1939 р. був порушенням польсько-німецького Договору про ненапад (січень 1934 р.), за що агресор має понести покарання (репарації та територіальні втрати). Польсько-радянський кордон визначений Ризьким договором 1921 р. Вторгнення 17 вересня 1939 р. було актом агресії, а відтак і порушенням радянськопольського Договору про ненапад (25 липня 1932 р.), за що агресор, згідно із нормами міжнародного права, повинен бути покараний. Ця остання вимога була тимчасово знята після досягнення домовленостей з Союзом РСР у липні 1941 р. Емігрантський уряд повністю ігнорував появу в міжвоєнному міжнародному праві нової реалії – визнання права націй на самовизначення. Уперше воно було задеклароване у т. зв. 14 пунктах президента США В. Вільсона (8 січня 1918 р.) і активно застосовувалося під час перекроювання європейських міждержавних кордонів Версальською конференцією. Крім того, вимоги “історичних прав” Польщі на Східну Пруссію та інші (східно)німецькі території в середині ХХ ст. виглядали відвертим анахронізмом. Тим самим емігрантський уряд Польщі відмовив українцям, білорусам і навіть Литві (уже як Литовській РСР) у визнанні їхньої державності, зводячи етнотериторіальний спір до вирішення питання про “польсько-російський кордон”. У цьому слабкість польської позиції. Слабкість радянських контраргументів у тому, наскільки “плебісцити” в Західній Україні, Західній Білорусії (жовтень 1939 р.) і передавання Віленщини Литві відповідали тогочасним міжнародно-правовим нормам. Позиція “не тільки плаща, але й ґудзика не віддамо”, якої послідовно дотримувалися уряди В. Сікорського, С. Миколайчика та Т. Арцишевського, виглядає, на перший погляд, відірваною від реальності, а відтак і неефективною. Однак на основні поступки в питанні післявоєнних східних кордонів Польщі (Білосток, Перемишль, Сувалки та ін.) Москві довелося погодитися саме через протистояння з “неадекватними емігрантами”. Лояльний до Кремля Польський уряд національної єдності (ПУНЄ) на переговорах із радянською стороною улітку 1945 р. зумів додатково “виторгувати” на відтинку польсько-українського кордону лише невелику ділянку в Бескидах із Галичем і Тарніцею на схід від Устрик Горних (т. зв. обмін територіями 1951 р. тут до уваги не беремо). Тож територіальні набутки Польщі (післявоєнної ПНР) і, відповідно, територіальні втрати України (післявоєнної УРСР) мусимо зарахувати передусім на конто польських емігрантських урядів у Лондоні.

The international legal arguments and direct activities of the Polish emigrant governments of V. Sikorski (October 1939 – July 4, 1943), S. Mykolaychyk (July 1943 – November 1944), and T. Artsyszewski (1944–1947) on the issue of defining the postwar borders of Poland, including a section with the Ukrainian SSR. An attempt to assess the effectiveness of their activities was made. The main outlines of foreign policy of the emigrant government and a comprehensive set of international legal arguments, which would be used during the Second World War and after its end have already been formed in the autumn of 1939: Pacta sunt servanda. The German attack on Poland on September 1, 1939 – a breach of the Polish-German Non-Aggression Treaty (January 1934) by the Germans, for which the aggressor must be punished (reparations and territorial losses). The Polish Soviet border was defined by the Treaty of Riga in 1921. The invasion on September 17, 1939 was an act of aggression, and thus a violation of the Soviet-Polish Non-Aggression Pact (July 25, 1932), for which the aggressor must be punished in accordance with international law. This last requirement was temporarily withdrawn after reaching an agreement with the USSR in July 1941. At the same time, the emigrant government completely ignored the emergence of a new reality in interwar international law – the recognition of the right of nations to self-determination. It was declared for the first time in the so-called 14 points of President Wilson (January 8, 1918), and was actively used in the redrawing of European interstate borders by the Versailles Conference. Besides this, the requirements of “historical rights” of Poland to East Prussia and others (eastern) German territories in the middle of the twentieth century looked like an outright anachronism. Therefore the Polish emigrant government denied Ukrainians, Belarusians, and even Lithuania (already as the Lithuanian SSR) the recognition of their statehood, reducing the ethno-territorial dispute to resolving the issue of the “Polish-Russian border”. The weakness of the Polish position was in this. The weakness of the Soviet counterarguments was the extent to which the “plebiscites” in Western Ukraine, Western Belarus (October 1939) and the transfer of the Vilnius region to Lithuania corresponded to the international legal norms of the time. The position “not only the cloak, but also the button will not be given away”, which was consistently followed by the governments of V. Sikorsky, S. Mykolaychyk and T. Artsyshevsky, at first glance, seems to be detached from the reality, and therefore not effective. Nevertheless, Moscow's main preliminary concessions on the issue of Poland’s postwar eastern borders (Bialystok, Przemyśl, Suwalki, etc.) were made precisely in opposition to “inadequate emigrants”. The Polish Government of National Unity (PGNU), which was loyal to the Kremlin, in negotiations with the Soviet side in the summer of 1945 on the section of the Polish-Ukrainian border managed to “bargain” only a small area in the Beskids with Halych and Tarnitsa on the east of Ustryk Horny (the so-called territory exchange in 1951 is not taken into account here). The territorial gains of Poland (the post-war Polish People’s Republic) and, accordingly, the territorial losses of Ukraine (post-war Ukrainian SSR) must be attributed primarily to the accounts of Polish emigrant governments in London.
The position of polish anti-communist governments on the issue of state-territorial status of lesser eastern poland – malopołska wschodnia (western ukraine and western belarus) in 1939-1945 (aspects of geopolitics and international law). Part 2. from rapture of diplomatic relations (april 1943) to soviet-polish agreements 1945
Keywords: польсько-радянський територіальний спір 1939–1945 рр.; міжвоєнне (1918–1939 рр.) міжнародне право; т. зв. нове міжнародне право; міжнародні відносини періоду Другої світової війни; Polish-Soviet territorial dispute of 1939–1945; interwar (1918–1939) international law; so-called new international law; international relations during the period of the Second World War; 340.15